Attenuated baroreflex sensitivity in normotensive prediabetes and diabetes in Indian adults. (2nd April 2016) - Keerthi, Gorantla Shravya; Pal, Pravati; Pal, Gopal Krushna; Sahoo, Jaya Prakash; Sridhar, Magadi Gopalakrishna; Balachander, Jayaraman
ABSTRACT: Purpose/aim of the study : Though attenuated baroreflex sensitivity (BRS) is known to promote cardiovascular disease (CVD) risk in diabetics, its status in prediabetes has not been reported. Also, the link of BRS to CVD risk in normotensive diabetics has not been reported. This study aimed to evaluate the association of BRS to CVD risk in normotensive prediabetics and diabetics. Materials and methods : Participants ( n = 154) of 18–45 years were divided into normoglycemics ( n = 52), prediabetics ( n = 64) and diabetics ( n = 38) based on American Diabetes Association criteria. Body mass index, waist–hip ratio, waist–height ratio, body fat mass index, basal heart rate, systolic blood pressure, diastolic blood pressure, rate pressure product, BRS, heart rate variability (HRV), fasting plasma glucose, fasting insulin, lipid profile and atherogenic index of plasma (AIP) were measured. Indian Diabetes Risk Score (IDRS) and homeostatic model assessment of insulin resistance were calculated. Results : There was significant increase in all the parameters except BRS, HRV and high-density lipoprotein in prediabetics and diabetics compared to normoglycemics. All these parameters were significantly altered in prediabetics compared to diabetics. Significant negative correlation was found between BRS and other parameters in prediabetics and diabetics. Conclusions : BRS was attenuated in normotensive prediabetics and diabetics with high IDRS, insulin resistance, AIP, dyslipidemia and reduced HRV that predisposes them to CVD risk. The study demonstrates CVD risk quite early in the prediabetics with reduced HRV, high body fat, hyperinsulinemia, insulin resistance, AIP and rate pressure product.